PENGEMBANGAN POTENSI KEPEMIMPINAN KADER ORGANISASI SOSIAL KEMASYARAKATAN - Roy Setiawan; Dedy Triyono (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2023)
Leadership potential must be developed in an effective and efficient way to improve self-quality and organizational performance. This service activity is carried out with the aim of exploring the leadership potential of young generations as cadres or prospective leaders of social organizations as national cadres, so it is hoped that these cadres can lead the organization well as a miniature of a pluralistic society. This leadership potential development activity is essential to carry out with the hope of becoming a positive contribution to cadres to equip them to carry out their duties as leaders of social organizations.